2016
DOI: 10.1111/ijac.12585
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Mechanical Properties in a Hot‐Pressed Boron Carbide

Abstract: Effects of microstructure and material properties on the mechanical behavior of hot‐pressed boron carbide are presented. The microstructure and intrinsic microstructural inhomogeneities have been characterized using scanning electron microscopy characterization techniques (SEM/EDS/EBSD). In situ mechanical characterizations of the boron carbide microstructure and its larger inhomogeneities have been performed by nanoindentation. Macroscopic dynamic and quasi‐static compressive responses have been studied in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…To this end, an accurate analysis of hardness and elastic modulus as well as conductivity and their grain size dependence is essential for advanced applications. In this sense, previous studies have shown a relatively wide range of hardness values by Vickers indentation ~20-35 GPa [3][4][5][6][7][8][9][10][11][12][13] and nano-indentation  40GPa as well as elastic modulus 500GPa [14][15][16][17][18][19]. This large variation is mainly related to the presence of porosity in boron carbide ceramics, their grain-size effects, the composition and the indentation load.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, an accurate analysis of hardness and elastic modulus as well as conductivity and their grain size dependence is essential for advanced applications. In this sense, previous studies have shown a relatively wide range of hardness values by Vickers indentation ~20-35 GPa [3][4][5][6][7][8][9][10][11][12][13] and nano-indentation  40GPa as well as elastic modulus 500GPa [14][15][16][17][18][19]. This large variation is mainly related to the presence of porosity in boron carbide ceramics, their grain-size effects, the composition and the indentation load.…”
Section: Introductionmentioning
confidence: 99%
“…[43,17,45]. One advantage of a subset of the recent experimental literature is that much of the work was performed on samples taken from a single plate of a commercially available material that has been very well characterized [46,43], thus ensuring relative consistency of the microstructure.…”
Section: Dynamic Fracture Of Boron Carbidementioning
confidence: 99%
“…[7][8][9]40,41 The chemical and volume ch pany ceramization of the polymer during documented in several studies. that has been very well characterized, 43,46 thus ensuring relative consistency of the microstructure.…”
Section: Dynamic Fracture Of Boron Carbidementioning
confidence: 99%
“…Since all these models attempt to estimate an intrinsic component of hardness in an ideal single crystal, experimental hardness measurements on single crystals 4,25 can be used to test their accuracy. Furthermore, low‐load (≤50 mN) nanoindentation measurements 26‐28 may also be utilized based on the reasoning that the small length‐scales and loads at which indentation is conducted minimizes the influence of extrinsic factors (eg, porosity, grain‐size etc) on measured hardness. This comparison is accomplished in Figure 4 (and Table 2) where hardness estimated by BR (Aydin et al, 20 and Guo et al 15 ), BS, and modified EN models (purple, blue, and orange open symbols, respectively) for polymorphs across the homogeneity range are compared to experimental data (filled symbols).…”
Section: Influence Of Stoichiometry On Hardnessmentioning
confidence: 99%
“…Comparison of hardness values for different stoichiometries of boron carbide predicted by BR,15,20 BS, and modified EN models (open symbols) with experiments (filled symbols). Data colored blue were measured on single crystals4,25 while the rest are nanoindentation studies26,27,28 [Color figure can be viewed at wileyonlinelibrary.com] Polymorphs predicted to be present in boron carbide at various stoichiometries and their estimated hardness…”
mentioning
confidence: 99%